Views of discrimination among individuals confronting genetic disease. - Klitzman R (Journal of Genetic Counseling, 2010)
Though the US passed the Genetic Information Non-Discrimination Act, many questions remain of how individuals confronting genetic disease view and experience possible discrimination. We interviewed, for 2 hours each, 64 individuals who had, or were at risk for, Huntington's Disease, breast cancer, or Alpha-1 antitrypsin deficiency. Discrimination can be implicit, indirect and subtle, rather than explicit, direct and overt; and be hard to prove. Patients may be treated 'differently' and unfairly, raising questions of how to define 'discrimination', and 'appropriate accommodation'. Patients were often unclear and wary about legislation. Fears and experiences of discrimination can shape testing, treatment, and disclosure. Discrimination can be subjective, and take various forms. Searches for only objective evidence of it may be inherently difficult. Providers need to be aware of, and prepared to address, subtle and indirect discrimination; ambiguities, confusion and potential limitations concerning current legislation; and needs for education about these laws. Policies are needed to prevent discrimination in life, long-term care, and disability insurance, not covered by GINA.